FUERZA DE LA COMPETENCIA EN EL SECTOR PERIODÍSTICO: El Caso de los Diarios Formales de Lima - Antonio, Javier (1996)
Applying Porter's methodology of the well-known five competitive forces to analyze the nature of competition, this article seeks to demonstrate that the competitive advantages obtained by the companies are a function of the structure of the industry and the strategies developed by the intervening companies. To this end, we analyze the Peruvian print journalism sector, that of non-specialized newspapers, exponents of a formal style of presentation of information and aimed at traditional readers, a segment made up of: El Comercio, Expreso, La Republica and La Nación. The results show that, of the five competitive forces, the most relevant for the segment studied are the high barriers to entry, mainly due to the high levels of investment and know-how required; the permanent possibility of substitution by television and radio; and the bargaining power of clients, exercised by distribution agents and advertisers. It can be said that there are two aspects on which the newspapers analyzed have developed their competitive advantages: the barriers created and the positioning achieved.